Penerapan Media Pembelajaran Audiovisual Plotagon untuk Meningkatkan Kemampuan Menyimak Teks Berita Siswa Kelas VII UPTD SMP Negeri 1 Gunungsitoli Utara - Lase, Ricardo Sondrara; Ndruru, Mastawati; Halawal, Noibe; Waruwu, Lestari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study was motivated by the suboptimal news text listening skills of Grade VII-A students at UPTD SMP Negeri 1 Gunungsitoli Utara. Initial assessments revealed that some students struggled to comprehend key information, identify news content, and accurately restate the information they had heard. The study aimed to improve news text listening skills through the implementation of Plotagon audiovisual learning media. A Classroom Action Research (CAR) method was employed, conducted over two cycles, each comprising the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 32 students from class VII-A during the 2025/2026 academic year. Data were collected via observation, tests, documentation, and field notes, and subsequently analyzed using both quantitative and qualitative methods. The research results indicate that following the implementation of the Plotagon audiovisual medium in Cycle II, students' news text listening skills improved. The average student score rose from 58.28 in Cycle I—with a class mastery rate of 41%—to 79.21 in Cycle II, with a class mastery rate of 84%. This improvement was accompanied by increased teacher activity and student engagement during the learning process. Thus, the use of the Plotagon audiovisual medium in Cycle II supported the improvement of news text listening skills among Grade VII-A students.